2019
DOI: 10.18592/let.v9i1.3077
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Difficulties in Writing Recount Text at Inclusion Classes

Abstract: Writing skill is already taught in school and colleges. The students of Junior High School should retells something that already happened (Recount text). The objective of the study is to identify the students’ difficulties in writing recount text in inclusion classes. The study belongs to a mixed-method research involving 30 students of 8th grade inclusion class. The data collecting techniques was testing. There were several steps to analyze the data: analyzing the students’ work, calculating the average score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…It is defined as a systematic departure in learners' evolving knowledge of the target language rule system. The second is the competence factor which refers to the lack of understanding of the target language's rules Husna and Multazim (2019) Error identification serves three purposes. First, it gives teachers how far the students have progressed toward their objective and what they still need to learn.…”
Section: The Description Of Errorsmentioning
confidence: 99%
“…It is defined as a systematic departure in learners' evolving knowledge of the target language rule system. The second is the competence factor which refers to the lack of understanding of the target language's rules Husna and Multazim (2019) Error identification serves three purposes. First, it gives teachers how far the students have progressed toward their objective and what they still need to learn.…”
Section: The Description Of Errorsmentioning
confidence: 99%
“…The other problem in starting an essay is to correspond every clause into a cohesive and coherent text (Meiarista & Widhiyanto, 2020). Furthermore, the students face the problem of writing recount text in terms of content, organization, grammar, mechanic, and generic structure in orientation and re-orientation (Husna & Multazim, 2019). It occurs because the students do not understand the Theme and Rheme enough.…”
Section: Introductionmentioning
confidence: 99%
“…Based on an interview with an English teacher of SMP Pelangi Dharma Nusantara, it was found that grammatical errors was frequently committed by the eighth grade students when writing, especially recount text. It is a text that retells sequent of a past event in order to inform or entertain the reader (Husna & Multazim, 2019). It tells the person who involved, what he/she experienced, where and when it occurred.…”
Section: Introductionmentioning
confidence: 99%
“…,Ilmiah (2016), Yudari (2017), Fridayanthi (2017) Asni and Susanti (2018),Husna and Multazim (2019),and Tarigan, et al (2019).…”
mentioning
confidence: 99%